(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Coral fish are fish that are associated with coral reefs and their existence is determined by the variety and complexity of coral reefs. The purpose of this study was to analyze the dynamics of species richness and abundance of reef fish in several locations on the coral reefs of Liukangloe Island, Bulukumba District and their relation to live and dead coral cover. The research method was used LIT to know life and dead coral cover and Visual Census to record of reef fish. The data was done at 6 stations and each at 2 depths (3-5 m and 8-10 m) with 3 repetitions of transects (area: 80 m2). The species number and abundance of fish between stations were analyzed by ANOVA, while between depth was analyzed by t-student. The relationship between fish species richness and abundance and life and dead coral cover was done by regression and corelation analysis. The species number at a depth of 3-5 m according to the observation periode was very dynamic and showed significant differences between stations, while at depths of 8-10 meters, relatively stable and no different between stations. The abundance of fish at a depth of 8-10 meters was higher at 3-10 meters. Stations with high live coral cover was showed a higher species number of reef fish and was significantly different from stations with low live coral cover, but not in terms of abundance. Although positively correlated, the relationship between live coral cover and the number and abundance of reef fish were relatively weak. Conversely, negatively correlated with high dead coral cover.